2008
DOI: 10.1111/j.1600-0870.2007.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

A local ensemble transform Kalman filter data assimilation system for the NCEP global model

Abstract: The accuracy and computational efficiency of a parallel computer implementation of the Local Ensemble Transform Kalman Filter (LETKF) data assimilation scheme on the model component of the 2004 version of the Global Forecast System (GFS) of the National Centers for Environmental Prediction (NCEP) is investigated. Numerical experiments are carried out at model resolution T62L28. All atmospheric observations that were operationally assimilated by NCEP in 2004, except for satellite radiances, are assimilated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 25 publications
1
139
0
4
Order By: Relevance
“…A detailed derivation of the algorithm and its theoretical basis can be found in Hunt et al (2007) and Szunyogh et al (2008).…”
Section: Ensemble Data Assimilation At Cnmcamentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed derivation of the algorithm and its theoretical basis can be found in Hunt et al (2007) and Szunyogh et al (2008).…”
Section: Ensemble Data Assimilation At Cnmcamentioning
confidence: 99%
“…This larger value than the one used in the previous study (700 km: Bonavita et al, 2008) has been found to provide more accurate analysis and forecasts. Following Szunyogh et al (2008), the influence of each observation on the analysed grid point is decreased with its geophysical distance r through multiplication of the R −1 observation error matrix entries in Eqs. (1) and (3) with a smoothly decaying function of r (Gaussian with standard deviation equal to half the value of the radius of the local region).…”
Section: Ensemble Data Assimilation At Cnmcamentioning
confidence: 99%
“…The EnKF has been tested across a large range of forecast scales, from convective (Zhang et al, 2004) and mesoscale applications (Zhang et al, 2006;Meng and Zhang, 2007 and references therein) to regional and global scales (Dirren et al, 2007;Whitaker et al, 2008), with models and observational datasets of different realism. More recently, an efficient variant of the EnKF algorithm called Local Ensemble Transform Kalman Filter (LETKF) has been proposed and tested in global Numerical Weather Prediction (NWP) analysis and forecasting systems (Hunt et al, 2007;Miyoshi and Yamane, 2007;Szunyogh et al, 2008), comparing favourably with currently operational 3D-Var analysis systems.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there may occur non-zero forecast error covariances at long distances, and the number of leading model operator's eigenvectors may be larger than the number of ensemble members. This is the reason why some authors suggest using the ensemble algorithm locally (Hunt et al, 2007;Szunyogh et al, 2008). As follows from formula (7) for the elements of matrix , this matrix is the same for all grid points where analysis is carried out.…”
Section: A Version Of the π -Algorithm Based On Ensemble Forecastingmentioning
confidence: 99%
“…In the present article the formulae of the ensemble π -algorithm are derived from assumptions that are more general than those in Klimova (2008b). The operation count of the algorithm is close to that of the local ensemble transform Kalman filter (LETKF; Hunt et al, 2007;Szunyogh et al, 2008), but its formulae differ from those of the LETKF. In particular, the ensemble π -algorithm does not require calculating an ensemble that corresponds to the analysis error covariances because it is done automatically.…”
Section: Introductionmentioning
confidence: 99%